2017
DOI: 10.3945/ajcn.117.158089
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation directed at the prefrontal cortex of subjects with obesity reduces snack food intake and hunger in a randomized trial

Abstract: Obesity is associated with reduced activation in the left dorsolateral prefrontal cortex (DLPFC), a region of the brain that plays a key role in the support of self-regulatory aspects of eating behavior and inhibitory control. Transcranial direct current stimulation (tDCS) is a noninvasive technique used to modulate brain activity. We tested whether repeated anodal tDCS targeted at the left DLPFC (compared with sham tDCS) has an immediate effect on eating behavior during ad libitum food intake, resulting in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 47 publications
3
68
1
1
Order By: Relevance
“…This pattern was reflected by a reduction in the number of "yes" decisions for high-calorie food items that received very high palatability ratings. Taken together, these results, which are in line with beneficial effects on eating behavior of transcranial direct current stimulation of dlPFC activity in obese subjects (Gluck et al, 2015;Heinitz et al, 2017;Montenegro et al, 2012), suggest improved self-control during food choices after the neurofeedback intervention in our obese and overweight individuals. While we did not observe significant correlations between selfregulation performance in individual training ROIs with pre-post differences in body weight, body fat, or behavioral outcomes, the strong correlation between the decrease in palatability ratings and functional connectivity-derived dlPFC-right insula regulation provides a direct link between training-induced neural changes and improvements in food intake control.…”
Section: Behavioral Effectssupporting
confidence: 76%
“…This pattern was reflected by a reduction in the number of "yes" decisions for high-calorie food items that received very high palatability ratings. Taken together, these results, which are in line with beneficial effects on eating behavior of transcranial direct current stimulation of dlPFC activity in obese subjects (Gluck et al, 2015;Heinitz et al, 2017;Montenegro et al, 2012), suggest improved self-control during food choices after the neurofeedback intervention in our obese and overweight individuals. While we did not observe significant correlations between selfregulation performance in individual training ROIs with pre-post differences in body weight, body fat, or behavioral outcomes, the strong correlation between the decrease in palatability ratings and functional connectivity-derived dlPFC-right insula regulation provides a direct link between training-induced neural changes and improvements in food intake control.…”
Section: Behavioral Effectssupporting
confidence: 76%
“…The left dorsolateral prefrontal cortex (DLPFC), which is part of the dorsal cognitive fronto-striatal circuit, exerts cognitive control over food intake [38]. Obesity is associated with a reduced activation of this brain region [61]. Its postprandial activation is significantly inferior in the obese compared to in the lean [62].…”
Section: Areas Of the Cortexmentioning
confidence: 99%
“…The primary findings reported in Heinitz et al (3) are that stimulating the neurons in the left DLPFC reduced snack intake and self-reported hunger after an extended 4-wk stimulation period compared with sham treatment. However, no change was reported immediately after 3 sessions of tDCS on 3-d ad libitum intake assessed with a validated vending machine protocol.…”
mentioning
confidence: 95%
“…Second, do we understand the role of the DLPFC in driving overconsumption? Heinitz et al (3) found no effect on 3-d ad libitum food intake assessed by a validated vending machine paradigm. The foods included in the vending machine were those that had "intermediate" preference ratings as indicated by a food preference questionnaire.…”
mentioning
confidence: 97%
See 1 more Smart Citation